Bandgap-engineered proteinic near-infrared nanodots for localized precision cancer theranostics - Mou Seung Kim; In Ho Nam; Hyung Joon Cha; Yun Kee Jo (Journal of Nanobiotechnology)
Abstract Silver sulfide (Ag2S) quantum dots hold tremendous potential as promising near-infrared (NIR) theranostic agents for cancer treatment owing to their exceptional photophysical properties and deep tissue penetration capabilities. However, their complex synthesis process under harsh reaction conditions and poor retention at the target site still restrict clinical applications. Herein, metalloprotein adhesive nanodots biomineralized using engineered silver-binding mussel protein (MAP-AgP35) are presented as biosafe, high-performance photosensitizers to enable NIR-triggered theranostics for local cancer treatments. By constructing donor-acceptor pairs within the nanostructures through interfacial adhesive bridging between the MAP-AgP35 and Ag2S minerals, the sticky proteinic Ag2S nanodots dramatically reduced the energy bandgap for enhanced light absorption; this enables remarkably efficient superoxide radical (·O2 −) generation and photothermal conversion (η ~ 59%), in addition to effective fluorescence emission in the second NIR (NIR-II) region. The outstanding optochemical functionalities of these nanodots allow direct eradication of cancer cells via effective photodynamic and photothermal actions in the presence of an 808 nm NIR laser, with good biocompatibility toward normal cells. Importantly, these biomineralized nanodots overcome major limitations of conventional photosensitizers, offering a clinically translatable theranostic platform for realizing precise and complete ablation of cancer in a minimally invasive manner. Graphical abstract